Transport properties of Ba3Ca1+xNb2−xO9−δ composite perovskite oxides - Yu-shi DING; Ying LI (工程科学学报, 2021)
ABO3-type perovskite oxides and A3B′B′′2O9-type composite perovskite oxides exhibit proton conduction from 200 ℃ to 1000 ℃. These high-temperature proton conductors have received considerable attention due to their promise as electrolytes in fuel cells, electrolytic hydrogen production, hydrogen separation, electrochemical reactors, sensors, etc. The Ba3Ca1+xNb2−xO9−δ composite perovskite-type solid electrolyte has stable chemical properties and corrosion resistance to CO2 and H2O, so it can be used in long-term electrochemical devices. Protons are incorporated into Ba3Ca1+xNb2−xO9−δ in a humid or hydrogen-containing atmosphere because of the reaction of H2O and oxygen vacancies in proton conductors. However, proton conductors also exhibit oxygen vacancy conduction in the high-temperature range. In addition, electron holes can be generated by an oxygen vacancy reaction with atmospheric oxygen, causing proton conductors to exhibit electron-hole conduction. Hence, more oxygen vacancies can be produced with more Ca2+ dopant in Ba3Ca1+xNb2−xO9−δ due to a lack of positive charge. Meanwhile, the proton and electron-hole concentrations increase with oxygen vacancies, and the conductivity of Ba3Ca1+xNb2−xO9−δ can be improved. However, the crystal structure of Ba3Ca1+xNb2−xO9−δ can be changed with Ca2+ doping, and changes in proton, oxygen vacancy, and electron-hole transport numbers, the ratio of protons, oxygen vacancies, and electron-hole conductivity to total conductivity respectively, are unknown with Ca2+ doping, with different effects of crystal structure for protons, oxygen vacancies, and electron-hole conduction. Ba3Ca1+xNb2−xO9−δ has high conductivity in a humid atmosphere, and the proton transport number with doping amount needs to be further studied. In this work, Ba3Ca1+xNb2−xO9−δ (x=0, 0.10, 0.18, and 0.30) with a composite perovskite phase was prepared using a solid-state reaction method. With the increase in Ca2+ doping amount, the conductivity of Ba3Ca1+xNb2−xO9−δ samples first increased and then decreased, and the conductivity of the sample with x=0.18 was the highest. The electron-hole transport number of Ba3Ca1+xNb2−xO9−δ under the atmosphere containing hydrogen was relatively low. Protons were mainly conductive carriers in Ba3Ca1+xNb2−xO9−δ below 750 ℃, while Ba3Ca1+xNb2−xO9−δ exhibited mainly oxygen vacancy conduction at 800 ℃. With the increase in dopant amount, the oxygen vacancy transport number of Ba3Ca1+xNb2−xO9−δ increased gradually, while the proton transport number decreased gradually.